A new species of anole from Parque Nacional Volcán Arenal, Costa Rica (Reptilia, Squamata, Dactyloidae: Norops) - Köhler, Gunther; Vargas, Joseph (Zootaxa, 2019)
We describe the new species Norops arenal sp. nov. from Parque Nacional Volcán Arenal, north-central Costa Rica. In external morphology and genetic similarity of the 16S DNA barcode, Norops arenal is most similar to N. altae, N. fortunensis, N. fuscoauratus, N. gruuo, N. kemptoni, N. monteverde, N. pseudokemptoni, and N. tenorioensis. In morphology it shares with these species the following characteristics: (1) short hind limbs; (2) a single elongate prenasal scale; (3) tiny, smooth, often juxtaposed body scales; and (4) a slender habitus, often delicate. Norops arenal differs from these species, among several scalation details, by having a blackish central area in the male dewlap in life and in preservative (vs. no suffusion of black pigment on male dewlap in the other species), and a small red female dewlap in life (vs. dirty white, cream colored, or orange); extremely short hind legs with the tip of fourth toe of the adpressed hind leg reaching only to level of shoulder (vs. usually at least to level of ear in the other species); a short tail with a tail length/SVL ratio of 1.53 in single specimen with complete tail (vs. this ratio >1.6 in the other species); and a tiny size with 41.5 mm in single known adult male and 38.5 mm in single known adult female (vs. SVL of adults usually >42.0 mm). It further differs from N. altae, N. fuscoauratus, N. gruuo, N. pseudokemptoni, and N. tenorioensis by having a unilobed hemipenis (vs. bilobed in these five species).